Application Of The A-Star Algorithm On The Mapping Of Sports Team In The City Of Pematang Siantar Based On Android - Gunawan, Gunawan; Suendri, Suendri (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Geographic information system is a system that has the function to build, store, manage, and display information related to geography. This geographic information system is very helpful for human work in any case. This Android-based GIS application design produces complete information and can be accessed online or can download the application on our cellphones. Currently the city of Pematang Siantar is developing, especially in the field of technology. This research designs a technology that can help people to find a shortest route solution in searching for information on sports teams and their training locations in the city of Pematang Siantar using the A-Star algorithm. The A-Star algorithm is very helpful because the time to find the nearest route is faster and the routes found can be different but at the same cost, making it easier for designers to code in worksheets. The results of this study are in the form of an android application that is connected to the internet network so that it makes it easier for people to find information about sports teams and the closest location to where the user is using only a mobile phone and anywhere that is reachable by the internet network. This android application displays detailed information about sports teams, training locations, and training schedules controlled by the admin who is responsible for adding and changing sports team data so that the application runs properly.